Positional distribution of transcription factor binding sites in the human genome - Chun-Ping Yu; Zhi Thong Soh; Maloyjo Joyraj Bhattacharjee; Wen-Hsiung Li (PLoS ONE, 2025)
As transcription factors (TFs) play a major role in gene regulation, we studied their binding motifs (positional weight matrices, PWMs) and binding sites (TFBSs) in the human genome, and how TFs bind DNA motifs, including the involvement of binding co-factors. Using the chromatin immunoprecipitation sequencing data recently released by ENCODE (Encyclopedia of DNA Elements), we obtained new PWMs for 196 TFs and revised PWMs for 119 TFs. From these and the PWMs previously obtained for 235 TFs, we inferred the canonical PWMs for 500 TFs, including 243 new PWMs. Analysis revealed that most TFBSs are in introns (42.6%) and intergenic regions (31.6%), with only 11.3% in promoters. However, the TFBS density is considerably higher in promoters, showing a bell-shaped distribution of TFBSs with a peak at the transcription start site. Many TFBSs lie close to CTCF (CCCTC-binding factor) binding sites. Tethered binding is far more frequent than co-binding, with the latter often requiring co-factors.